OUTCOME ANALYSIS FOR PATIENTS WITH SEVERE COMPOUND FRACTURES OF LOWER EXTREMITY LONGITUDINAL BONES IN THE REGIONAL GENERAL HOSPITAL - A. N. Blazhenko; S. N. Kurinniy; A. A. Blazhenko; A. V. Shevchenko (Инновационная медицина Кубани)
Background. We have performed outcome analysis in patients treated for severe compound fractures of lower extremity longitudinal bones regarding a chosen treatment technique for initial surgical debridement and transfer terms in the regional general hospital.Material and Methods. We reviewed 151 patient reports treated in Scientific Research Institute – Ochapovsky Regional Clinical Hospital no. 1, Krasnodar, for 2012–2016. We defined four methods for initial surgical debridement at the first stage of surgery. Outcomes were analysed in patients regarding their initial surgical debridement and transfer terms into the regional general hospital from the primary admission sites.Conclusion. It is required to work out regional system for staged treatment in patients with severe compound fractures. At first stage initial surgical treatment is performed by techniques no. 2, 3 and then patients are transferred to the regional general hospital during the first day after being injured. In unstable patients initial surgical debridement should be divided in two stages.